澳門品德與公民教育校本課程初探 - Tchiang, I.; Ge, Yun (2020)

Enhancing Educational Collaborations between China and SIngapore - Saw, Swee-Hock; Ge, Yun (Advancing Singapore-China Economic Relations, 2014)

Education and human capital management in a world city: the case of Singapore - Ho, K. C.; Ge, Yun (Asia Pacific Journal of Education, 2011)
There is considerable evidence to suggest that the human capital needs of the world city differ from what Robinson calls “ordinary cities” or what Markusen and associates term as “second tier cities”. This path is blazed most notably in the field of world cities and the flow of skilled labour, in the work by Sassen and with case examples (finance, law, accountancy) provided in the work by Beaverstock and his associates. This focuses on producer services and migration flows needs to be matched by an accompanying look at city-based strategies. This paper represents an attempt to provide this by providing a case history analysis of Singapore in three stages of growth – as port city, industrial city and as world city – in order to show how the evolving infrastructure associated with human capital (education, immigration and labour policies) allows human capital to be developed, attracted, harnessed, deployed, released and retained.
15 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/02188791.2011.595058
Keywords: Singapore; human capital; migration

Belt and Road Initiatives: implications for China’s internationalisation of tertiary-level education - Ge, Yun; Ho, Kong Chong (Educational Research and Evaluation, 2022)
Since the launch of the One Belt and One Road Initiative (BRI) in 2013, the internationalisation of China’s tertiary education has entered a new stage. Central to the BRI is investment and strategic planning for talent cultivation, knowledge production, and transmission. This paper explains how the BRI redirects, reinforces, and intensifies China’s strategic planning and actions for internationalising its education. It adopts a policy analysis approach and reviews three key aspects of development and shifting emphasis of internationalisation under the impact of the BRI: international education networks along the Six BRI Economic Corridors, vocational colleges as new players in international education, and promotion of the Chinese language as a new global language. The analysis captures an important moment in which international education processes are being visibly altered through China’s strategies to take the lead in economic globalisation and to compete for a central place in the world via the BRI.
0 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/13803611.2022.2041858
Keywords: Belt and Road Initiatives; Chinese language; Internationalisation of higher education; vocational education

Conceptualizing the Second Education Circuit for China’s Doctoral Students in Asia - Ge, Yun; Ho, Kong Chong (International Journal of Chinese Education, 2019)
The quest to become research universities of international repute has led flagship universities in East and Southeast Asia to develop a new focus on attracting international doctoral students. This paper aims to understand Chinese doctoral students’ mobility in the immediate region and their education to work perceptions. The study draws from a sample of 301 doctoral students from China who were studying at five universities in Japan, South Korea, and Singapore. Analysis on students’ decision making and after-study pathways highlights the regional exchange in related areas. We argue that this regional mobility of doctoral students, characterized as the second education circuit, is facilitated by a higher education migration infrastructure with three interactively weaved dimensions: commercial, social, and regulatory. The research findings suggest the growing importance of Asia as a regional second circuit of doctoral training for students from China.
1 citations (Crossref) [2022-09-21]

International Student Diversity Experiences in their Host Cities - Ge, Yun; Ho, Kong Chong (National University of Singapore and Université Paris Cité, 2022)

Intra-Asia higher education mobilities - Ge, Yun; Ho, Kong Chong (Routledge Handbook of Asian Migrations, 2017)
Intra-Asian higher education mobility is a relatively new phenomenon in Asia and one triggered by the dynamic economic changes occurring in East Asia,
Publication Title: Routledge Handbook of Asian Migrations

Researching international student migration in Asia: research design and project management issues - Ge, Yun; Ho, Kong Chong (Journal of Population Research, 2014)
In the context of Asia, the changing dynamics of higher education has increased the visibility and significance of the group of intraregional education migrants. There are several methodological issues which need to be addressed in conducting research for this group of migrants. First, how does the particular type of migrant group and Asian context influence the research design? Second, in order to capture the scale and diversity of this migrant group, how should research be conducted across multiple sites? Third, how does a mixed method design allow researchers to learn more about the behaviour, practice and orientations of education migrants? Our paper aims to make contributions to the discussions on the methods of education migration research in Asia through answering these questions. We use research experiences and preliminary data from a multinational project to illustrate the issues involved in the selection of methods, research design and project management.
2 citations (Crossref) [2022-09-21]
Keywords: Asia; Higher education; International student migrants; Mixed methods; Multi-site design; Multicultural research

The Cultivation of Research Labor in Pacific Asia with Special Reference to Singapore - Ge, Yun; Ho, K. C. (Asia Pacific Education Review, 2018)
This paper adopts a political economy perspective in understanding how the country context frames the development of higher education doctoral science, technology, engineering, and mathematics (STEM) programs. We argue that a country's commitment to research and development spending as a strategy to maintain its economic competitiveness creates the market for research labor. This embeddedness of STEM doctoral training programs in the country's science and technology system enlarges differences between STEM and non-STEM doctoral programs. This argument is validated from a survey of doctoral students in leading Pacific Asian universities which shows that STEM doctoral programs have stronger research networks, are better financed, use better facilities, and incorporate a variety of research placements. The embeddedness of STEM programs is further illustrated from the case of Singapore. Singapore-based STEM doctoral students mention enjoying better financial support and receiving better career advice from their supervisors. They depend on collaborative peer learning and cite more varied employment options when asked about their career plans.
9 citations (Crossref) [2022-09-21] Publisher: Springer
Keywords: Career Counseling; Cooperative Learning; Doctoral Programs; Educational Facilities; Employment Opportunities; Financial Support; Foreign Countries; Graduate Students; Networks; STEM Education; Student Attitudes; Student Placement; Student Research; Student Surveys; Supervisor Supervisee Relationship; Universities

Career Planning of Doctoral Students in Macau: Linking Individual Experience to Macro Picture - Ge, Yun (2022)

Career trajectory and cross-system mobility: Career planning of doctoral students in Macao - Ge, Yun (Higher Education Quarterly, 2024)
This study investigates career trajectory and work locations of doctoral students trained in Macao and analyses how their career paths are shaped by perceived macro-level factors. Respondents from four applied disciplinary areas were selected for semi-structured in-depth interviews. Research results show that doctoral students who graduated from Macao higher education institutions enjoy good career prospects in Mainland China. Their competitiveness in the research-related job market benefits from having a multi-level support system and a training mode that promotes government–university–industry collaboration. Policies and demand from industrial sectors are involved in students' learning experience through channels such as financial support, project collaboration and networks. Doctoral students in Macao are strategic planners and actors in leveraging their human capital. As Macao becomes an emerging destination for cultivating high-level research labour, findings from this study capture a model of human capital formation in China's cross-system context.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/hequ.12474
Keywords: career trajectory; cross-system mobility; doctoral education; employability; human capital formation

Internationalisation of higher education: new players in a changing scene - Ge, Yun (Educational Research and Evaluation, 2022)
0 citations (Crossref) [2022-09-21] Publisher: Routledge _eprint: https://doi.org/10.1080/13803611.2022.2041850

Postgraduate Certificate Program of Education in University of Saint Joseph: Cultivating the Rationales and Techniques of Culturally Responsive Teaching among Teachers in Macau (“聖若瑟大學學位後證書課程: 澳門教師文化关联教學理念和技能的培養”in Chinese) - Ge, Yun (University of Saint Joseph, 2018)

The Role of University in High-Level Human Capital Cultivation in China’s West Greater Bay Area - Ge, Yun (2022)

Understanding Chinese Model of Government-University-Industry Collaborations in Research and Education: The Case of Macau SAR. - Ge, Yun (2023)
Higher Education in Macau has been benefiting from a multi-layered institutional environment under China’s One-Country-Two-Systems. This presentation introduces research and education policies and practices of Macau universities under China’s national plan of the Greater Bay Area development. It aims to demonstrate and analyze how higher education actors collaborate with local and regional governments and industrial sectors in human capital formation and research innovations.

澳門教師文化回應教學認知與實踐研究 - Ge, Yun (2021)

澳門課程改革與發展: 政策與實務 - Ge, Yun (2022)

澳門特殊與融合教育的發展及教師培訓 - Ge, Rochelle Yun (2023)

課程變革的趨勢和具澳門特色的課程發展 - Ge, Rochelle Yun (2023)